2011
DOI: 10.1177/1075547010377879
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Exposures: Scientific Controversy, the Media, and Public Responses to Bisphenol A

Abstract: The controversy surrounding the potential health effects of bisphenol A (BPA) has recently spread from the scientific arena to mass mediated public debate. This study presents a theoretical account of low-information rationality to explain why media use (including newspaper use and online health information use) and confidence in key actors (including business, the Food and Drug Administration, and scientists) may predict public responses to BPA. It then analyzes survey data to examine how these factors are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Higher study level was a predictor of both better knowledge and safer practices. As a matter of fact, higher education has been linked with greater knowledge about science and technology in general (16), and BPA in specific (11). Moreover, highly educated people were shown to be more attentive to scientific controversies and topics discussed in the news, although this was not always associated with greater factual knowledge (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher study level was a predictor of both better knowledge and safer practices. As a matter of fact, higher education has been linked with greater knowledge about science and technology in general (16), and BPA in specific (11). Moreover, highly educated people were shown to be more attentive to scientific controversies and topics discussed in the news, although this was not always associated with greater factual knowledge (17).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been only a few studies assessing the level of familiarity, knowledge, attitude, and practices concerning BPA. A study conducted in the US showed that 70% of the people surveyed had at least heard about BPA, which were considered to be familiar with the topic (11). In Thailand, a study showed that while parents and health professionals know about some of the adverse effects of BPA, they do not know how to use or purchase plastic products properly, showing a lack of knowledge despite some familiarity with the topic (12).…”
Section: Despite All the Evidence The Most Recent Risk Assessments Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Using survey methods, researchers in the USA have shown that attitudes toward Bisphenol A are shaped primarily by news exposure, trust in business and trust in the USA regulator, the Food and Drug Administration. These surveys indicate that more exposure and less trust is associated with more negative views of Bisphenol A (Brewer and Ley 2011). Other researchers have explored the potential for scientific ambiguity to influence Bisphenol A judgements, and found that when people are told ‘there is not enough scientific evidence that Bisphenol A harms human health’ this significantly reduces their support for a Bisphenol A ban (Maxim and Mansier 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Research in Science Studies, Sociology, and Rhetoric has explored how scientific controversy shapes public discourse [Brewer and Ley, 2011;Friedman, Dunwoody and Rogers, 1999;Gregory and Miller, 1998;Priest, 2006]; yet, little research has explored how scientific controversy affects the way that science deployed in academic or professional settings. One exception might be Robert Proctor's [2008] study of "agnotology."…”
mentioning
confidence: 99%